Evaluation Results of an Ontology-based Design Model of Virtual Environments for Upper Limb Motor Rehabilitation of Stroke Patients - Ramírez-Fernández, Cristina; Morán, Alberto L.; García-Canseco, Eloísa; Gómez-Montalvo, Jorge R. (Methods of Information in Medicine, 2017)
Objectives: 1) To enhance the content of an ontology for designing virtual environments (VEs) for upper limb motor rehabilitation of stroke patients according to the suggestions and comments of rehabilitation specialists and software developers, 2) to characterize the perceived importance level of the ontology, 3) to determine the perceived usefulness of the ontology, and 4) to identify the safety characteristics of the ontology for VEs design according to the rehabilitation specialists.Methods: Using two semi-structured Web questionnaires, we asked six rehabilitation specialists and six software developers to provide us with their perception regarding the level of importance and the usability of the ontology. From their responses we have identified themes related to perceived and required safety characteristics of the ontology.Results: Significant differences in the importance level were obtained for the Stroke Disability, VE Configuration, Outcome Measures, and Safety Calibration classes, which were perceived as highly important by rehabilitation specialists. Regarding usability, the ontology was perceived by both groups with high usefulness, ease of use, learnability and intention of use. Concerning the thematic analysis of recommendations, eight topics for safety characteristics of the ontology were identified: adjustment of therapy strategies; selection and delimitation of movements; selection and proper calibration of the interaction device; proper selection of measuring instruments; gradual modification of the difficulty of the exercise; adaptability and variability of therapy exercises; feedback according to the capabilities of the patient; and real-time support for exercise training.Conclusions: The rehabilitation specialists and software developers confirmed the importance of the information contained in the ontology regarding motor rehabilitation of the upper limb. Their recommendations highlight the safety features and the advantages of the ontology as a guide for the effective design of VEs.
Keywords: Virtual environment; stroke; design; motor rehabilitation; ontology